Lariat ethers with a novel proton-ionisable groups: new generation of collectors in ion flotation process. (1st January 2011) - Maciejewski, Pawel; Ulewicz, Malgorzata; Robak, Waldemar; Walkowiak, Wladyslaw
The influence of aqueous solution pH on the flotation rate and flotation efficiency with lariat ethers possessing cavities from DB-13-C-4 to DB-22-C-7 and four different acidic groups (sulphonamide, sulphonic, carboxylic, phosphonic) was studied. The correlation between the maximal percent removal of mentioned cations, the initial concentration of lariat ether and the non-ionic foaming agent, and the pH of aqueous solution as well as molar intrinsic volume and Hydrophilic–Lipophilic Balance (HLB) of studied ethers was found.